Rotman Lens-Based Wide Angular Coverage and High-Gain Semipassive Architecture for Ultralong Range mm-Wave RFIDs - Eid, Aline; Hester, Jimmy G. D.; Tentzeris, Manos M. (IEEE antennas and wireless propagation letters, 2020)
In this letter, the authors demonstrate, for the first time, the implementation of a fully-flexible, energy autonomous Rotman lens-based backscattering RFID tag operating in the 28 GHz 5G band. The Rotman lens front end was designed, simulated, fabricated on a thin flexible substrate and its gain and differential radar cross section (RCS) tested. The structure displays a simultaneous high gain and wide angular coverage, resulting in a remarkable RCS, measured in both planar and severe bending conditions. A low power oscillator was then added to the retrodirective array to test its detectability as a backscatterer at an unprecedented range of up to 64 m while displaying a power consumption as low as 2.64 μ W, effortlessly supplied by its flexible solar cell in normal office indoor conditions. Enabled by the implementation of a high degree of focalizing retrodirectivity, this unique Rotman lens-based system could enable the birth of RFIDs with practical reading ranges exceeding 1.8 km.